Histopathological and immunohistochemical evaluation of primary muscular peripheral T cell lymphoma in a dog - Fonseca-Alves, Carlos Eduardo [UNESP] (2017)
Background: Canine lymphoma is the most common hematopoietic neoplasm in dogs and reveals divergent biological behaviors correlated to histopathological subtype, the immunophenotypic (T or B) and tumor stage. The multi-centric form is the most common presentation for canine lymphoma, followed by gastrointestinal and cutaneous forms. Miscellaneous forms of canine lymphoma (nasal, osseous, central nervous system and muscle) represent less than 1% of all cases. This report describes the clinical, macroscopic, histopathological and immunohistochemical findings detected in a dog with a primary muscular lymphoma. Case: The subject was referred to the Emergency and Critical Care Service at the Veterinary Hospital with a history of claudication in the left pelvic limb, severe dehydration, hypovolemia, vomiting and diarrhea caused by gastroenteritis associated with the use of phenylbutazone. After death, the post-mortem examination revealed ulcerative gastritis in the gastrointestinal tract (GIT). Histopathological examination of the GIT specimens, mesenteric lymph nodes, and the left popliteal lymph node revealed no neoplastic alterations. Histological examination of semitendinosus muscle revealed proliferation of cells with round or oval nucleus, an evident pleomorphic nucleolus and scanty, eosinophilic cytoplasm. There were five to six mitosis per each 400x field. These cells infiltrated through the muscle fibers. The muscle fibers displayed marked eosinophilic sarcoplasm, loss of striations and fragmentation (degeneration). Immunohistochemical staining revealed negative reaction for CD79a and positive for CD45 and CD3. Discussion: The primary muscle lymphoma it is very rare disease and patients commonly have clinical signs related with muscle location. Our description of muscular primary lymphoma affecting the semitendinosus muscle emphasize that it must be included as a differential diagnosis for dogs with unilateral lameness, inflammatory processes, and other malignancies. In this case, the patient showed an ulcerative gastroenteritis associated with the inappropriate use of phenylbutazone. The patient death was associated with a septicemia due to several ulcers in the gastrointestinal tract. We excluded any regional lymph node involvement and secondary muscular infiltration with post-mortem and histopathological examination. The gross evaluation of the left hind limb demonstrated only muscular involvement (semitendinosus muscle) without infiltration in the adjacent structures, and the histopathology revealed no alteration in the regional lymph node. The immunohistochemical evaluation showed negative staining to CD79a, a high number of positive cells to Ki67 and positive staining to CD45 and CD3. In normal lymph nodes, it was possible to note CD79 diffuse expression in germinal centers in lymphoid follicles and few positive B-lymphocytes in medullary region. Diffuse CD3 expression was found in cortex region by normal T-lymphocytes. There was no histological alterations in sublumbar and popliteal lymph nodes. This immunohistochemical and histological patterns revealed a Peripheral T Cell lymphoma with a high proliferative index. The previous report of primary muscular lymphoma showed a T cell lymphoma with a high proliferative index similar to our findings. Based on macroscopic, histopathological, and immunohistochemical findings it was concluded that the patient had a primary muscular Peripheral T Cell lymphoma.